2006
DOI: 10.1186/1471-2431-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Screening for hypoglycemia at the bedside in the neonatal intensive care unit (NICU) with the Abbott PCx glucose meter

Abstract: BackgroundPoint of care (POC) glucose meters are routinely used as a screening tool for hypoglycemia in a neonatal setting. Glucose meters however, lack the same accuracy as laboratory instruments for glucose measurement. In this study we investigated potential reasons for this inaccuracy and established a cut off value for confirmatory testing.MethodsIn this prospective study, all patients in the neonatal intensive care unit who had a plasma glucose test ordered were eligible to participate. Demographic infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 17 publications
2
28
0
2
Order By: Relevance
“…A similar tendency has been described in many previous reports of studies performed using other conventional BG meters. 5,8,9 According to our results, there was a positive bias of approximately 30% in the measurements obtained when the Hct value was 10%. This indicates that a PG level of 2.78 mmol=L (50 mg=dL) corresponds to a WBG level of 3.61 mmol=L (65 mg=dL) when the Hct value is 10%.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A similar tendency has been described in many previous reports of studies performed using other conventional BG meters. 5,8,9 According to our results, there was a positive bias of approximately 30% in the measurements obtained when the Hct value was 10%. This indicates that a PG level of 2.78 mmol=L (50 mg=dL) corresponds to a WBG level of 3.61 mmol=L (65 mg=dL) when the Hct value is 10%.…”
Section: Discussionmentioning
confidence: 64%
“…However, as reported previously, many studies performed using conventional BG meters and methods identical to those used in the present study have reported that the Hct values have similar effects on the measurements. 5,[8][9][10] Some of the results obtained for BG meters tested in previous studies are as follows: y ¼ À1.161x þ 0.339, GLUTEST NEO SUPER CORRECTS HEMATOCRIT EFFECT R ¼ À0.693, P < 0.001 for Glutest Neo (Sanwa Kagaku Kenkyusho Co. Ltd.) and y ¼ À1.661x þ 0.516, R ¼ À0.872, P < 0.001 for Precision Ò Xceed Ò (Abbott Diabetes Care, Abbott Park, IL). 5 Similar to the results of our present study, these results also indicated that the WBG levels are overestimated when the Hct value is low and underestimated when the Hct value is high.…”
Section: Discussionmentioning
confidence: 98%
“…Da dies nur in einer begrenz ten Anzahl von Einrichtungen gewährleis tet ist, wird meist auf bettseitige Messungen mit "point of care"Geräten ausgewichen. Viele handelsübliche Blutglukosemessstrei fen sind nicht auf neonatale Proben mit ihren potenziell hohen Hämatokrit und niedrigen Glukosewerten ausgerichtet und deshalb bei der Fahndung nach neonatalen Hypoglykämien nur bedingt tauglich [2,3,17,18,31,38,43,52,58,60]. Geräte, die pa rallel zu Glukose den Hämatokrit und die Nichtglukosezucker messen und für die se korrigieren, scheinen akzeptable Werte zu ergeben, publizierte Vergleichsmessun gen im Bereich niedriger Glukosekonzen trationen mit neonatalen Proben sind je doch spärlich [7,64].…”
Section: Introductionunclassified
“…Many POC devices have been shown to be inadequate in this setting. [40][41][42][43] Point-of-care device test strips using glucose oxidase (see later) are prone to errors caused by oxygen effects. Tang and colleagues showed that errors of 15% or more could occur with highly oxygenated blood samples (i.e., PaO 2 >100 mm Hg), 44 and variances of up to 46% from reference values have been observed under hyperbaric conditions.…”
Section: Terminologymentioning
confidence: 99%